Pendidikan keluarga dalam perspektif Islam - Kamali, Moh; Nawawi, Nawawi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Education that takes place in the family carried out by parents as their duty and responsibility to educate in the family. The relationship between individuals in the family environment greatly affects the child's psyche and the impact will be seen until later when he reaches adulthood. A loving and conducive atmosphere for intellectual development that is successfully built in a family will make a child able to adapt to himself, his family and the surrounding community. The family as the first educational environment is very important in shaping the pattern of the child's personality, because in the family the child is first acquainted with values and norms. Family education provides basic knowledge and skills, religion and beliefs, moral values, social norms and views of life that students need to be able to play a role in the family and in society.